Behavioural change to promote the adoption of agronomic solutions - Ofosu-Ampong, Kingsley; Muller, Anna; Abera, Wuletawu (2024)
This report provides an overview of how behaviour change is addressed across the EiA Use Cases. It represents an effort of the Behaviour Change Group (BCG) to document how the behaviour change occurs. The report draws on experiences from 10 EiA Use Case Leads, as well as insights from the use case profiles depicting behaviour change strategies. The report documents behavioural insights and challenges to behaviour change, and highlights the behaviour change principles identified in the Use Cases. The Use Case countries include Bangladesh, Cambodia, Vietnam, Ethiopia, Ghana, India, Kenya, Morocco and Nigeria. Fifteen of the twenty Use Case leads were invited to contribute, with ten responding and engaging in a behaviour change discussion and reporting. This report offers an overview of behaviour change initiatives undertaken within the EiA Use Cases, highlighting key lessons learned.